Characterization of Wet and Dry Deposition in the Downwind of Industrial Sources in a Dry Tropical Area - Raj K. Singh; Raj M. Agrawal (The Scientific World Journal)
An atmospheric deposition study was conducted in the downwind of Shaktinagar Thermal Power Plant (STPP), Renusagar Thermal Power Plant (RTPP), and Anpara Thermal Power Plant (ATPP), at Singrauli region, Uttar Pradesh (UP), India to characterize dry and wet deposition in relation to different pollution loading. During the study period, dry and wet depositions and levels of gaseous pollutants (SO2 and NO2) were estimated across the sites. Dry deposition was collected on a monthly basis and wet deposition on an event basis. Depositions were analyzed for pH, nitrate (NO3), ammonium (NH4+), and sulphate (SO42) contents. Dry deposition rate both collected as clearfall and throughfall varied between 0.15 to 2.28 and 0.33 to 3.48 g m2 day1, respectively, at control and maximally polluted sites. The pH of dry deposition varied from 5.81 to 6.89 during winter and 6.09 to 7.02 during summer across the sites. During the rainy season, the mean pH of clear wet deposition varied from 6.56 to 7.04 and throughfall varied from 6.81 to 7.22. The concentrations of NO2 and SO2 pollutants were highest during the winter season. Mean SO2 concentrations varied from 18 to 75 g m3 at control and differently polluted sites during the winter season. The variation in NO2 concentrations did not show a pattern similar to that of SO2. The highest NO2 concentration during the winter season was 50 g m3, observed near RTPP. NO2 concentration did not show much variation among different sites, suggesting that the sources of NO2 emission are evenly distributed along the sites. The concentrations of NH4+, NO3, and SO42 ions in dry deposition were found to be higher in summer as compared to the winter season. In dry deposition (clearfall) the concentrations of NH4+, NO3, and SO42 varied from 0.13 to 1.0, 0.81 to 1.95, and 0.82 to 3.27 mg l1, respectively, during winter. In wet deposition (clearfall), the above varied from 0.14 to 0.74, 0.81 to 1.82, and 0.67 to 2.70 mg l1, respectively. The study clearly showed that both dry and wet depositions varied between the sites and season, suggesting significant impact of industrial activities in modifying the atmospheric input. The nonacidic deposition suggests that there is no threat of acidification of the receiving ecosystem at present.